1999
DOI: 10.1557/s109257830000315x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Ion Implantation in Gallium Nitride

Abstract: Epitaxial single crystal GaN films (2.0 µm thick) were implanted 60° off the <0001> surface normal with 600 keV O + ions at 190 or 210 K over a range of ion fluences from 4.8×10 17 to 5.0×10 20 ions/m 2 . The implantation damage, as determined by in-situ Rutherford Backscattering Spectrometry in a <0001> channeling geometry (RBS/C), ranged from dilute defects up to the formation of a disorder saturation state that was not fully amorphous. The relative disorder on the Ga sublattice exhibited a sigmoidal depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…9,10 The TEM experiments in the present study were performed on a specimen irradiated to a fluence of 215 O + ions/nm 2 at room temperature. The films were epitaxially grown on (0001) sapphire substrate by metalorganic vapor phase epitaxy (MOVPE) and possessed a high-crystalline quality, as evidenced by a minimum yield of approximately 1.7% for the Ga sublattice under RBS/C analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The TEM experiments in the present study were performed on a specimen irradiated to a fluence of 215 O + ions/nm 2 at room temperature. The films were epitaxially grown on (0001) sapphire substrate by metalorganic vapor phase epitaxy (MOVPE) and possessed a high-crystalline quality, as evidenced by a minimum yield of approximately 1.7% for the Ga sublattice under RBS/C analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Ion implantation is a critical technique to spatially dope selective donor and acceptor ions into GaN for fabrication of advanced optoelectronic devices. These efforts include the development of appropriate methods for growing high-quality, single-crystal GaN thin films, 1,2 the correlation of its electrical and optical properties with its microstructure, 1,3 and ion-implantation-related phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…This reflects the complexity of the damage buildup in GaN under SHI bombardment and the oversimplification of the defect overlap model. 38 It should be noted that previous studies 2,4,39,40 have revealed a rather complex damage buildup behavior in GaN under keV ion bombardment, including the effect of damage saturation in the crystal bulk. Figure 4 suggests that a somewhat similar damage saturation effect may also be present in GaN under SHI bombardment, but additional work is currently needed to clarify it.…”
Section: A Damage Accumulationmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] In particular, it has been revealed that, under a wide range of implant conditions, irradiation-induced microstructural evolution involves the formation of planar defects on the basal plane of the wurtzite structure. 2,9 Although such irradiation-produced defects in GaN have previously been studied in cross-sectional transmission electron microscopy ͑XTEM͒ specimens by the diffraction contrast imaging technique, 2,9 the atomic structure of these defects has not been characterized, and, hence, their nature and the formation mechanisms are still unknown.…”
mentioning
confidence: 99%